1996
DOI: 10.2116/analsci.12.747
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Equilibrium of the Distribution of 2-Thenoyltrifluoroacetone in Carbon Tetrachloride-Aqueous Perchlorate Solution Systems

Abstract: The rate and equilibrium of the liquid-liquid distribution of 2-thenoyltrifluoroacetone (Htta) was studied in carbon tetrachloride-aqueous 0.1 mol dm-3 sodium perchlorate solution systems at 298 K. The distribution equilibrium of Htta reached after two-phase agitation for 90 min and the distribution constant of the total Htta was 2.2X10; however, that of the enol form of Htta was higher than 2X102 and that of the keto form of Htta was 5.8X10'. By a spectrophotometric method and by a liquid-liquid partition met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The observed rate constant of ketonization in water-saturated carbon tetrachloride was 1070 s-1, as was given in ref. 9. This is more than two orders lower than the values of kobsd in Fig.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The observed rate constant of ketonization in water-saturated carbon tetrachloride was 1070 s-1, as was given in ref. 9. This is more than two orders lower than the values of kobsd in Fig.…”
Section: Discussionmentioning
confidence: 55%
“…This is due to the absorption by the enol form Htta; the absorption by the keto form is negligible at this wavelength. 9 It was also found that the absorption of carbon tetrachloride solution of TOPO at this wavelength was negligible.…”
Section: Spectrophotometry Of Carbon Tetrachloride Solutionsmentioning
confidence: 94%
“…Such a chemical equilibrium is illustrated by the presence of an isobestic point in figures 1 and 2. As already mentioned in literature, one of the parameters driving the keto/enol equilibrium is the polarity of the solvent [14]. In addition, obviously, the enol/hydrate equilibrium depends on the total water amount in the solvent in which TTA is dissolved.…”
Section: Discussionmentioning
confidence: 94%
“…It is well known that TTA forms adduct or ion-pair with trioctylphosphine oxide (TOPO) to create a synergistic effect, which increases the extraction efficiencies of metallic ions. Many researchers studied solvent extraction of metallic ions using TTA and TOPO [7][8][9][10][11][12][13][14][15][16]. Noro and Sekine [11] studied the synergistic extraction of lanthanide using TTA with TOPO or tetrabutylammonium ions (TBA ? )…”
Section: Introductionmentioning
confidence: 99%
“…and reported the distribution coefficient and equilibrium constant. Sekine et al [12][13][14][15] also performed several researches on the solvent extraction of metallic ions with the same extractants. Takazawa et al [16] reported thermodynamic study on the synergistic extraction of cobalt (II) with b-diketone and TTA.…”
Section: Introductionmentioning
confidence: 99%